Analisis Anak Angkat dalam Perspektif Hukum Islam, Status dan Kedudukannya - Istiawati, Sri (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2024)
During the time application of child become power of district court very Islam. Law number 3 year 2006 concerning change of law number 7 year 1989 concerning Islamic court, giving power to justice of religion to accept, to checking, and judging and also of child genesis and lifting of child pursuant to law of Islam. Stipulating of lifting of child pursuant to Islamic law by justice of religion do not decide contractual terms or lineage relation / link with old fellow contain him. foster child judicially remain to confess as child contain from old fellow contain him. Foster child in law of Islam nor make that foster child as child contain or likened by the child him and rights of like child contain and illegal foster parent become sponsor do woman foster child marry.